2020
DOI: 10.1186/s40510-020-00336-2
|View full text |Cite
|
Sign up to set email alerts
|

One versus two anterior miniscrews for correcting upper incisor overbite and angulation: a retrospective comparative study

Abstract: Background: Miniscrews are effective devices for performing upper incisor intrusion. Different mechanics can be applied depending on the treatment objectives. This study aimed to evaluate the efficacy of one or two anterior miniscrews for upper incisor correction in cases of overbite and angulation in adult patients. Methods: Forty-four adults with deep overbite were divided into two groups: group 1 was treated with one miniscrew between upper central incisors and group 2 with two miniscrews between upper late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Alsamak et al [ 39 ] concluded in their systematic review that the optimal site of placement of mini-implants in the anterior maxilla is between the canine and first premolar, whereas Fayed et al [ 40 ] concluded the optimal site is between the central and lateral incisors. Also, maxillary anterior intrusion with good control over buccal angulation is seen when using 2 mini-implants that are placed between the canine and lateral incisor on right as well as the left side, rather than a single midline implant, as reported by Vela-Hernández [ 41 ].…”
Section: Discussionmentioning
confidence: 84%
“…Alsamak et al [ 39 ] concluded in their systematic review that the optimal site of placement of mini-implants in the anterior maxilla is between the canine and first premolar, whereas Fayed et al [ 40 ] concluded the optimal site is between the central and lateral incisors. Also, maxillary anterior intrusion with good control over buccal angulation is seen when using 2 mini-implants that are placed between the canine and lateral incisor on right as well as the left side, rather than a single midline implant, as reported by Vela-Hernández [ 41 ].…”
Section: Discussionmentioning
confidence: 84%
“…The full text of the remaining 30 studies (21 studies by database search and 9 studies after manual search) were retrieved and analyzed, 5 of them because only the amount of vertical control of teeth during retraction was assessed and 10 of them were excluded because they did not have a mini-screw group. A total of 15 articles were included in our study for systematic review [ 15 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], and after data extraction, meta-analyses were performed on 14 studies, and for one study [ 42 ], only a systematic review was performed due to differences in outcomes and retainers under review with the rest of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding root resorption, in the evaluated studies, there was no significant difference between the groups in terms of the amount of root resorption, both linearly (Deguchi et al, Karagoz et al, Vela Hernandez et al) [ 15 , 40 , 44 ] and volumetrically (Liou et al) [ 42 ]. In all investigated intrusion groups, moderate root resorption in the apex (about 1 to 2 mm) was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method has been demonstrated to be efficient in deep overbite correction no matter with 1 or 2 miniscrews. [ 17 ] However, the usage of miniscrew is accompanied with multiple adverse effects, including biologic damage, inflammation, pain and discomfort. [ 18 , 19 ] With this method, at least 1 extra miniscrew needs to be inserted into maxillary anterior alveolar bone, which would increase the risk and cost and turn out to be not friendly enough for patients.…”
Section: Discussionmentioning
confidence: 99%